Dr. Megan Clark on food production and climate change in Australia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Australia already has one of the most variable climates in the world and the changes now underway will determine the "vibrancy of our region." How is climate change influencing food production and other aspects of life in Australia? Dr. Megan Clark is on the Commission on Sustainable Agriculture and Climate Change. Find out more at https://ccafs.cgiar.org/commission